Human wayfinding in the horizontal versus vertical plane. (August 2020) - Bock, Otmar; Fricke, Madeleine; Koch, Iring
Abstract: Experimental evidence suggests that our internal representation of surrounding space consists of a stack of horizontal planes. This outcome could reflect a fundamental property of human spatial cognition, or it could just reflect the asymmetrical permeability of buildings in which participants were tested, i.e., they had ample opportunity for looking and walking within a given level, but much less opportunity for looking and walking between levels. To find out we designed two grid-like mazes, a virtual and an imagined one, both with symmetrical permeability, and asked participants to find their way from a starting point to a goal once while the maze was oriented horizontally (condition H), and once while it was oriented vertically (condition V). We observed no significant differences between wayfinding performance in H and V, neither with the virtual nor with the imagined maze. This result provides no support for the view that internal representations in the form of stacked horizontal planes reflect a fundamental cognitive principle. Highlights: Used a grid maze with either a horizontal or a vertical orientation. Allowed similar opportunity for looking and walking in both orientations. Observed similar wayfinding performance in both orientations. Earlier-reported horizontal advantage may reflect physical setting, not cognition.